The Relationship Between Patient Safety Culture and Patient Satisfaction Level At Public Health Center Ajung Jember Regency - Irawati, Eni; Vitaliati, Trisna (LPPM Universitas dr. Soebandi, 2024)
Safety culture is an aspect of organizational culture that refers to how health workers see andtreat safety in a health service, which has implications for patient satisfaction. This study aimedto identify relationship between patient safety culture and the level of patient satisfaction atPublic Health Center Ajung Jember Regency.The research design used was cross-sectional,involving inpatients at Public Health Center Ajung Jember Regency as many as 45 respondents.The sampling technique uses simple random sampling. Data was collected using the Indonesianversion of the Hospital Survey of Patient Safety Culture and Service Quality questionnaire.Statistical analysis using Spearman rho test with significance ≤0.05. Most patients expressed ahigh category of patient safety culture (57.8%), with more than half (51.1%) expressingsatisfaction with services. There was a relationship between patient safety culture and patientsatisfaction (p-value = 0.000; α = 0.05; r = 0.694). Discussion: Patient satisfaction will alsoincrease by implementing a good patient safety culture. Therefore, training on theimplementation of patient safety culture is very necessary to be held for nurses at public healthcenter; in this case, the policy stakeholders who are obliged to hold the training.